Unioni civili e convivenze: la legge n. 76 del 2016 alla prova della giurisprudenza (Stato, Chiese e pluralismo confessionale, 2024)
Civil unions and cohabitations: the law. No. 76 of 2016 to the test of jurisprudenceABSTRACT: After a long and complex jurisprudential and political journey, Law no. 76 of 2016 introduced into Italy the legal figure of civil unions, which regulate the relationship between people of the same sex, and regulated cohabitation. A few years after the entry into force of the law, this work aims to highlight the evolution of legislation occurred thanks to the main jurisprudential rulings that concerned it.SOMMARIO: 1. Origini e fondamento costituzionale della legge sulle unioni civili e convivenze - 2. La legge n. 76 del 2016: struttura e criticità - 3. Le union civili - 4. Le convivenze - 5. La sentenza Corte cost. 22 aprile 2024, n. 66 - 6. La sentenza Corte cost. 25 luglio 2024, n.148 - 7. La sentenza Cass. civ. SS. UU. 27 dicembre 2023, n. 35969 - 8. Conclusioni.